2020
DOI: 10.1111/asj.13433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic supplementation on growth performance, intestinal morphology, barrier integrity, and inflammatory response in broilers subjected to cyclic heat stress

Abstract: Heat stress is one of the most challenging environmental stressors that influence poultry production worldwide, and causes large economic losses annually (Lara & Rostagno, 2013). High ambient temperature leads to diverse deleterious impacts on physiological, immunological, and performance traits in poultry (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 76 publications
4
19
0
Order By: Relevance
“…Another remarkable change observed in this study was the CHE can simultaneously affect multiple organ indexes (liver: ALT, AST, ALP, γ-GT, TBIL, DBIL, and IBIL; kidney: CREA-S and UA; heat: CK, LDH, and CK-MB), showing heat stress could cause dysfunction in multiple organs. These results concur with those of previous studies, suggesting response to CHE involves multiple organs and systems ( 23 , 61 ). In the present study, we also examined molecular indices of oxidative stress; it showed that birds subjecting to chronic heat exposure increased oxidative stress, as shown by lower levels of T-AOC, SOD, and GSH-Px with higher MDA concentrations in serum.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another remarkable change observed in this study was the CHE can simultaneously affect multiple organ indexes (liver: ALT, AST, ALP, γ-GT, TBIL, DBIL, and IBIL; kidney: CREA-S and UA; heat: CK, LDH, and CK-MB), showing heat stress could cause dysfunction in multiple organs. These results concur with those of previous studies, suggesting response to CHE involves multiple organs and systems ( 23 , 61 ). In the present study, we also examined molecular indices of oxidative stress; it showed that birds subjecting to chronic heat exposure increased oxidative stress, as shown by lower levels of T-AOC, SOD, and GSH-Px with higher MDA concentrations in serum.…”
Section: Discussionsupporting
confidence: 93%
“…Gut microbiota is now increasingly recognized as a hidden “metabolic organ” that plays a critical role in regulating the host metabolic homeostasis and energy balance, promoting the development and maturation of intestinal mucosa, maintaining intestinal barrier integrity in gut ( 22 , 23 ). A normal gut microbial community and complete mucosal morphology in birds are the bases for excluding pathogens and maintaining normal nutrient digestion and absorption ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results are compatible with the results of Al-Fataftah and Abdelqader ( 41 ) and Jahromi et al ( 42 ). On the other side, Li et al ( 43 ) reported that probiotic supplementation could improve the morphology of the intestine and barrier function and alleviate inflammatory response but has no effect on growth under heat exposure. Moreover, Sandikci et al ( 44 ) and Sohail et al ( 45 , 46 ) reported that probiotics have no effect on the growth of the broilers stressed with heat.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress on heat shock protein in the gutHeat-shock proteins (HSPs) are well-recognized as stress proteins and molecular chaperones that protect the internal cell environment by participating in protein folding, repair, localization and degradation influencing essential process such as cell signaling, transcription, protein synthesis, metabolism, and regulation of cellular redox conditions and thus regulating cell growth and survival[1,79,80]. The synthesis and expressions of HSP are stimulated under biotic and abiotic stress stimuli, particularly hyperthermia, oxidative stress, infections, diseases, and hypoxia, to protect cell proteins from oxidative stress and other harmful environmental conditions[79,80].…”
mentioning
confidence: 99%